Lemon Peel Water Extract: A Novel Material for Retinal Health, Protecting Retinal Pigment Epithelial Cells against Dynamin-Related Protein 1-Mediated Mitochondrial Fission by Blocking ROS-Stimulated Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase Pathway - Shang-Chun Tsou; Chen-Ju Chuang; Inga Wang; Tzu-Chun Chen; Jui-Hsuan Yeh; Chin-Lin Hsu; Yu-Chien Hung; Ming-Chung Lee; Yuan-Yen Chang; Hui-Wen Lin (MDPI AG, 2024)
Previous studies showed that NaIO3 can induce oxidative stress-mediated retinal pigment epithelium (RPE) damage to simulate age-related macular degeneration (AMD). Lemon peel is rich in antioxidants and components that can penetrate the blood-retinal barrier, but their role in retinal oxidative damage remains unexplored. Here, we explore the protection of lemon peel ultrasonic-assisted water extract (LUWE), containing large amounts of flavonoids and polyphenols, against NaIO3-induced retinal degeneration. We initially demonstrated that LUWE, orally administered, prevented retinal distortion and thinning on the inner and outer nuclei layers, downregulating cleaved caspase-3 protein expression in RPE cells in NaIO3-induced mice. The effect of LUWE was achieved through the suppression of apoptosis and the associated proteins, such as cleaved PARP and cleaved caspase-3, as suggested by NaIO3-induced ARPE-19 cell models. This is because LUWE reduced reactive oxygen species-mediated mitochondrial fission via regulating p-Drp-1 and Fis1 expression. We further confirmed that LUWE suppresses the expression of p-MEK-1/2 and p-ERK-1/2 in NaIO3-induced ARPE-19 cells, thereby providing the protection described above, which was confirmed using PD98059 and U0126. These results indicated that LUWE prevents mitochondrial oxidative stress-mediated RPE damage via the MEK/ERK pathway. Elucidation of the molecular mechanism may provide a new protective strategy against retinal degeneration.